Dural venous sinus thrombosis after traumatic brain injury - Girwal, Gaurawkant; Chaurasiya, A. K.; Dhurve, Lalit; Gaur, Rajneesh (International Surgery Journal, 2023)
Background: Dural venous sinus thrombosis (DVST) is a subset of cerebral venous thrombosis, and its presentation depends mainly on the sinus involved. The use of modern imaging techniques allows earlier diagnosis of DVST. Aims and objectives were to study the outcome and prognosis of DVST after head injury. Methods: This observational cross-sectional study was conducted in a tertiary care surgical intensive care unit (ICU) in central India on patients admitted to Gandhi Medical College, Bhopal, in the period from January 2020 to December 2020, suffering from traumatic brain injuries, suspected of dural venous sinus/cortical vein thrombosis. Glasgow coma scale (GCS) was recorded at the time of admission and regular follow-ups were every fortnightly done for 6 months. Statistical analysis was done with the help of Epi-Info 7 software. Results: The mean age of the patients was 43.78 years. The most common computed tomography (CT) finding was that temporo-occipital hemorrhage/edema was present in 12 (24%) patients, followed by frontotemporal hemorrhage/edema in 10 (20%) patients. Out of 50 suspected cases based on CT findings only 15 patients were confirmed with the diagnosis of DVST by MRV. There was a shift of patients from moderate and severe GCS to mild GCS in subsequent follow-up. Conclusions: Head trauma constitutes a potent risk factor for developing thrombosis of the dural venous sinus. Good imaging studies allow us to make an accurate diagnosis and timely management of these patients will give us good results.